(untitled) (Journal of Human Sciences, 2021)
The current researcher aimed to identify the standard of quality of life among students of the Faculty of Physical Education, Sebha University. The research concentrates on identifying the differences according to the variables gender and year of study. The researcher used the quality of life scale, prepared by Mansi and Kathem (2010). She used a sample of approximately (102) students, representing 60% of the participants. To verify the research hypotheses, the researcher used the T-test for one group, the T-test for two independent groups, and the analysis of variance ــ ANOVA. The results are: the level of feeling of quality of life among students of the Faculty of Physical Education at Sebha University is statistically significant in all dimensions of the overall score of the scale. There are no significant differences among students of the Faculty of Physical Education at Sebha University according to the variables gender and year of study, in the dimensions of the quality of life scale and the overall score of the scale.